SIMULATION-BASED LEARNING IN PETROLEUM EDUCATION: PEDAGOGICAL PRINCIPLES AND DIGITAL SOLUTIONS - Abdullaeva Asila Olimovna (Web of Journals Publishing, 2025)
The article is devoted to the issues of integrating simulation models into the professional education system of specialists in the oil and gas industry. The necessity of creating innovative educational spaces in the context of digitalization and the uncertainty of the production environment is substantiated. The pedagogical principles, forms, and means ensuring the effective implementation of simulation technologies in the educational process are described. An analysis of international experience has been carried out, and key directions for improving the effectiveness of student training based on simulation modeling have been identified.
Keywords: Simulation models, oil and gas education, digitalization, professional competence, reflection, simulation platforms, active learning methods.